The Psychological Innovation of Sports Broadcasting and Hosting Language in the Context of New Media - Yan Jing; Ying Jing (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Objective: In order to continuously improve the artistic language of sports broadcasting and hosting, and better adapt to the development trends of the industry, thereby promoting the overall level of sports broadcasting and hosting progress.This paper first puts forward that sports broadcasting should deal with three relationships and complete three relationships Innovation, finally achieve media convergence: the relationship between platform operation and content production, to solve the innovation of process reengineering; Frequency targeting and audience needs Seek the relationship, solve the service innovation; The relationship between listeners, fans, circles and users, to solve the innovation of broadcasting business model.The author studied the artistic characteristics and language psychological innovation strategies of sports broadcasting and hosting language based on the context of new media.Through analysis, it is shown that sports broadcasting hosts need to continuously improve their professional literacy, explore the hidden emotional attitudes in language, reflect the unique expressive charm in language, highlight the clear characteristics of the times in language, and regulate the innovation and individuality of language expression.In the context of new media, the domestic sports broadcasting and hosting field has won better development opportunities, the realization of personal professional development goals for sports broadcasting and hosting personnel and the requirements for innovative development in the media field cannot be separated from the strengthening of the artistic nature of sports broadcasting and hosting language.